Linking insomnia and OCD symptoms during the coronavirus pandemic: Examination of prospective associations - Cox, Rebecca C. (J Anxiety Disord, 2021)
There is considerable concern in the mental health community about the psychological consequences of the coronavirus pandemic and who may be most vulnerable. Obsessive-compulsive disorder (OCD) symptoms may be particularly sensitive to the context of the pandemic. Previous research suggests insomnia symptoms may contribute to increased OCD symptoms over time, particularly during times of stress, such as the pandemic. The present study examined pre-coronavirus outbreak insomnia symptoms as a predictor of post-coronavirus outbreak OCD symptoms in a sample of community adults who completed a 2016 survey study and were re-contacted on April 1, 2020 (N = 369). Results revealed a small significant increase in OCD symptoms following the coronavirus outbreak and a small significant decrease in insomnia symptoms. Pre-coronavirus outbreak insomnia symptoms significantly predicted increases in post-coronavirus outbreak OCD symptoms. Similar results were found for specific OCD symptom facets with the exception of washing and hoarding symptoms, which were unrelated to pre-coronavirus insomnia symptoms. There was no evidence for a reverse effect of prior OCD symptoms on insomnia symptoms during the pandemic. These findings suggest those with insomnia symptoms prior to the coronavirus pandemic may be vulnerable to increases in some OCD symptoms during the pandemic. The implications for preventing adverse psychological responses during the coronavirus pandemic are discussed.